Megalithic Culture in India with Special Reference to Chhattisgarh: Exploring the Megalithic Culture of India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Ancient Indian history is divided and studied through its periodization into Pre historic, Protohistoric and Historic phases. The Indian Megalithic culture is regarded as one of the proto historic cultures. The term ‘Megalith’ is combination of the Greek words – Megas meaning ‘big’ and lithos meaning ‘stone’. The Megalithic monuments are the most visible feature of cultures i.e., Megalithic cultures which are named after them. In functional terms, they served as sepulchral or memorial structures, symbolically marking the place where the megalithic people buried their dead and in this manner constitute the most noticeable physical markers of that age.